Metabolomics in quality formation and characterisation of tea products: a review. (29th April 2022) - Cai, Hongli; Zhong, Zhuoheng; Li, Zhanming; Zhang, Xiaojing; Fu, Hongwei; Yang, Bingxian; Zhang, Lin
Summary: Tea is one of the biggest categories of modern non‐alcoholic beverages with health benefits. Through different processes, tea products are divided into six main types: green tea, yellow tea, white tea, oolong tea, black tea and dark tea. Metabolomics is helpful for the comprehensive, accurate and rapid determination of tea metabolites in different types of tea products and tea processing materials. It has been widely applied in studying the relationship of tea metabolites and its quality. Therefore, it is necessary to summarise the application of metabolomics in tea. In this review, we described and summarised (1) the main metabolites of six types of tea and their implications on tea quality with emphasis on the content differences in the main metabolites in different types of tea; (2) the research on optimising the key processing steps of six types of tea based on metabolomics and the discussion of various new strategies for effectively improving their quality and (3) the advanced approach to characterise and distinguish different grades of tea products via metabolomics. The current review offers guidance for the improvement of tea quality by metabolomics and its potential challenges. Abstract : Interaction between quality identification of tea processing and metabolomics.